The Impact of Public Sector Wage Controls in Ontario - Auld, D.A.L.; Wilton, D.A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
This paper seeks to evaluate the effectiveness of Ontario's public sector wage and price controls in ternis of the rate of change in public sector wage